Effect of the acromial inferolateral tilt on subacromial impingement syndrome: a retrospective magnetic resonance imaging assessment - Vaz,André (2020)
Abstract Objective: To evaluate the effect of acromial inferolateral tilt on subacromial impingement syndrome. Materials and Methods: The acromial inferolateral tilt was retrospectively quantified by two researchers on 346 shoulder magnetic resonance images using the glenoacromial (between the inferior proximal acromial surface and the glenoidal face) and acromioclavicular (between the axis of the proximal acromion and distal clavicle) angles. Results: The glenoacromial angle was associated with subacromial impingement syndrome (p < 0.001) and complete supraspinatus tendon rupture (p < 0.001), and the acromioclavicular angle was associated with partial or complete supraspinatus tendon rupture (p = 0.003). The area under the receiver operating characteristic curve (AUC), best cut-off angle, and odds ratio (OR) of the glenoacromial angle for impingement syndrome were 0.579 (95% confidence interval [CI]: 0.508-0.649; p = 0.032), 72°, and 2.1 (95% CI: 1.136-4.053), respectively. For complete supraspinatus tendon rupture, the AUC, best cut-off angle, and OR of the glenoacromial angle were 0.731 (95% CI: 0.626-0.837; p = 0.001), 69°, and 8.496 (95% CI: 2.883-28.33), respectively. For partial or complete supraspinatus tendon rupture, the AUC, best cut-off angle and OR of the acromioclavicular angle were 0.617 (95% CI: 0.539-0.694; p = 0.002), 17°, and 3.288 (95% CI: 1.886-5.768), respectively. Interobserver agreement found for the glenoacromial and acromioclavicular angles were 0.737 (95% CI: 0.676-0.787; p < 0.001) and 0.507 (95% CI: 0.391-0.601; p = 0.001), respectively. Conclusion: Inferolateral acromial tilt may have some impact on subacromial impingement syndrome; however, the best quantification method identified (glenoacromial angle) showed a moderate interobserver agreement and a fair performance to assess the risk of complete supraspinatus tendon rupture.